Exploration of 77 GHZ automotive radar for intelligent transport system (ITS) applications - Tan, James Jin Yi (Nanyang Technological University, 2021)
Automotive radars are a very important safety component in many driver assistance systems today. They could be used in applications such as adaptive cruise control, parking sensors and blind spot monitoring sensors, amongst many others. This report presents a thorough study on the 77 GHz Automotive Radar for transport applications. The study involves several components, which include a literature review on the 77 GHz automotive radar, radar fundamentals, a simulation of the 77 GHz automotive radar in traffic scenarios and experiments being conducted on two 77 GHz automotive radars, namely including the NXP TEF810X radar and the AWR1642 BOOST radar.